EXPOSURE TO INTERFERON-β THERAPY IN EARLY PREGNANCY: A LITERATURE REVIEW OF PREGNANCY OUTCOMES IN WOMEN WITH MULTIPLE SCLEROSIS. (29th November 2012) - Hughes, S; Spelman, T; Gray, O; Boz, C; Trojano, M; Zwanikken, C; Lugaresi, A; Izquierdo, J; Duquette, P; Girard, M; Grand'Maison, F; Grammond, P; et al.
Abstract : Background: Pregnancy counselling is an important aspect of the care of women of childbearing age who have multiple sclerosis (MS). The issue of cessation of interferon therapy for conception and pregnancy still provokes debate within the MS community, given conflicting study findings. Here we present a review of the literature. Methods: A literature search was performed for studies examining the effect of interferon-β therapy on pregnancy outcomes in women with MS. This returned 12 eligible studies, reviewed by two independent reviewers. Results: In six studies data was collected retrospectively, prospectively in five studies and by both methods in one study and included a total of 1105 pregnancies 'exposed' to interferon. In 10 studies, there was no increase in the rate of spontaneous abortion or birth defects. Interpretation of studies finding a higher than expected rate of spontaneous abortion was limited by inadequate sample sizes. Conclusions: We found 1105 pregnancies in which the effect of interferon exposure was examined in women with MS. There is no evidence of unfavourable pregnancy outcomes in the majority of studies. Given the lack of proven adverse effects with interferon therapy in early pregnancy, neurologists could safely advise females with MS to continue treatment when planning conception.